2019
DOI: 10.15294/jpii.v8i3.19532
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Field Trip on Junior High School Students’ Naturalistic Intelligence and Problem-Solving Skill in Ecosystem Subject

Abstract: Naturalistic intelligence is a part of multiple intelligences, while problem-solving skills are part of higher-order thinking. Both are learning outcomes required to be developed and improved since these competences were considered poor in Indonesia. Field trip is a learning method that can encourage students to interact directly with the real object in nature. That learning method is expected to improve students' naturalistic intelligence and problem-solving skills. In this case, this research was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Finally, the results prove that the outdoor activities in the teaching and learning process can increase students' interest and achievement of science in the VIII-G class of SMP Negeri 1 Watampone. This result is supported by some research that also found that the outdoor activities can increase student interest and students' achievement (Adisendjaja et al, 2019;Aisah, 2015;Eick, 2012;Fägerstam, 2014;Kadir, 2016;Mackenzie et al, 2018;Ngabekti et al, 2017;Spalie et al, 2011;Ting & Siew, 2014;Wahyuni et al, 2017).…”
Section: Descriptive Analysis Of Final Test Results In the Second Cyclementioning
confidence: 53%
See 1 more Smart Citation
“…Finally, the results prove that the outdoor activities in the teaching and learning process can increase students' interest and achievement of science in the VIII-G class of SMP Negeri 1 Watampone. This result is supported by some research that also found that the outdoor activities can increase student interest and students' achievement (Adisendjaja et al, 2019;Aisah, 2015;Eick, 2012;Fägerstam, 2014;Kadir, 2016;Mackenzie et al, 2018;Ngabekti et al, 2017;Spalie et al, 2011;Ting & Siew, 2014;Wahyuni et al, 2017).…”
Section: Descriptive Analysis Of Final Test Results In the Second Cyclementioning
confidence: 53%
“…However, it is worth considering that teachers need to find solutions or other alternatives in managing student learning processes using natural events around them, without having to bring them into the laboratory room (Yaman, 2016). Other than that be useful for increasing the literacy of students' environments (Adisendjaja et al, 2019;Wilujeng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Students live in a world where diversity exists and plenty of issues and concerns to address such as health concerns, environment protection, economic growth, and many more. A study by Adisendjaja et al (2019) concluded that field trip influences students' naturalistic intelligence. The last four remaining positions belonged to kinesthetic intelligence, existential intelligence, and logical intelligence which placed 6th, 7th, 8th, and 9th.…”
Section: Discussionmentioning
confidence: 99%
“…Interpersonal intelligence is cultivated through dialogue, simulation, and presentation. Another noteworthy strategy is the use of field trips to tap into students' naturalistic intelligence, offering experiential learning and providing students with a practical interface with their environment, thus fostering their naturalistic propensities (Adisendjaja et al, 2019). Further expanding the repository of MIenriched teaching tools is the advocacy for the development of MI-centric teaching materials that amalgamate core subjects like science, social studies, mathematics, Islamic religious education, and language, thus emphasising the importance of such integration in Indonesian public schools (Liliawati et al, 2019).…”
Section: Qualitative Analysismentioning
confidence: 99%